(untitled) (Bangladesh Journal of Medical Microbiology, 2019)
Emerging and reemerging pathogens are global challenges for public health. In recent times, corona viruses have become the most important virus worldwide because of the occurrence of more than 2 thousand deaths caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in China. Rapid spread of the infection occurred in many countries. However, most cases of mortality have occurred in China. The Center for Diseases Control and Prevention and World Health Organization maintain a website that is updated frequently with new cases of SARS-CoV-2 infection. Here we provide a brief introduction to corona viruses and also discuss the outbreaks of recently identified SARS-CoV-2. Bangladesh J Med Microbiol 2019; 13 (2): 18-24